The impact of gamma irradiation on the quality of meat and poultry: A review on its immediate and storage effects - Mohamad Shahrimi Hashim; Salma Mohamad Yusop; Irman Abdul Rahman (Applied Food Research)
Gamma irradiation stands as a proven and efficient technology, elevating the safety, quality, and shelf life of meat and poultry. Its prowess lies in its capacity to eradicate harmful microbes and prolong shelf life without inducing radioactivity. The utilisation of gamma irradiation emerges as an energy-efficient, safe, and environmentally friendly method. Irrespective of dosage, the application of gamma irradiation significantly reduces microorganisms and moisture content, while concurrently enhancing TVBN, PV, TBARS, colour a*, and fat content. However, it caused no significant impact on pH, sensory properties, colour L* and b*, protein, and ash content. During storage, gamma-irradiated meat and poultry experience a decline in pH, sensory properties, colour a*, moisture, protein, and ash content. On the other hand, microbial load, shelf life, TVBN, PV, TBARS, and fat content increase, while colour L* and b* remain unchanged. Precise dosage selection is paramount to effectively manage these changes. This comprehensive review explores both current advancements and potential developments within the gamma-irradiated meat and poultry. It is imperative not only to scrutinize the effects of gamma irradiation utilisation across various muscle-based systems but also to examine its efficacy with the use of diverse packaging methods, alternative preservation techniques, functional food ingredients in food systems, and consumer acceptance studies across different regions. Such investigations will bolster understanding and application of gamma irradiation, ensuring its efficacy and acceptance within the meat and poultry industry.